IMPLEMENTASI KERJASAMA ASEAN “ASEAN OUR EYES” DALAM MENANGANI AKSI TERORISME OLEH FILIPINA - Ayuni, Devi; ., Pazli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research discusses how to implement the concept of ASEAN cooperation, namely ASEAN Our Eyes, in dealing with the issue of terrorism in the Philippines. ASEAN Our Eyes (AOE) is a regional collaboration to facilitate ASEAN in exchanging strategic information regarding ways to deal with transnational crime in the context of global security issues. ASEAN Our Eyes (AOE) was inaugurated on January 25, 2018 with six ASEAN member countries signing the cooperation, which was only ratified by all ASEAN members in October 2018 because not all ASEAN member countries immediately agreed to the ASEAN Our Eyes (AOE) cooperation concept. They argue that it is necessary to review this collaboration so that only in October 2018 will all ASEAN member countries ratify it. This research uses qualitative methods with data collection techniques through literature studies sourced from several books, journals, articles, and websites. This research uses the perspectives of institutional liberalism and cooperative security theory. The results of this paper indicate that the implementation of the ASEAN Our Eyes policy in the Philippines is going well with an effective impact. Keywords: ASEAN Our Eyes, Terrorism, Counter terrorism, Philippines